Molecular cloning and characterization of Saccharomyces cerevisiae RAD28, the yeast homolog of the human Cockayne syndrome A (CSA) gene. - Bhatia, P K (1996)
Cockayne syndrome patients exhibit severe developmental and neurological abnormalities. Cells derived from these patients are sensitive to killing by UV radiation and do not support the rapid repair of the transcribed strand of transcriptionally active genes observed in cells from normal individuals. We report the cloning of the Saccharomyces cerevisiae homolog of the Cockayne syndrome A (CSA) gene, which we designate as RAD28. A rad28 null mutant does not manifest increased sensitivity to killing by UV or gamma radiation or to methyl methanesulfonate. Additionally, the rate of repair of the transcribed and nontranscribed strands of the yeast RPB2 gene in the rad28 mutant is identical to that observed in wild-type cells following exposure to UV light. As previously shown for rad7 rad26 and rad16 rad26 double mutants, the rad28 null mutant shows slightly enhanced sensitivity to UV light in the presence of mutations in the RAD7 or RAD16 gene. Both rad28 and rad26 null mutants are hypermutable following exposure to UV light.